The antipsychotic-like effects of the mGlu group III orthosteric agonist, LSP1-2111, involves 5-HT(1A) signalling - Wierońska, Joanna M. (Springer-Verlag, 2013)
RATIONALE: Several studies have suggested that modulation of the glutamatergic system via metabotropic glutamate receptors (mGlu) could be a new way to achieve antipsychotic-like activity. LSP1-2111, the group III mGlu receptor orthosteric agonist, with a high affinity towards mGlu(4) receptors, was previously shown to exhibit antipsychotic-like action in animal models displaying positive symptoms of schizophrenia. OBJECTIVES: Here, we decided to investigate the possible role of LSP1-2111 in models of negative (social interaction) and cognitive (NOR) symptoms of psychosis. We also investigated the involvement of 5-HT(1A) receptors in the LSP1-2111-induced antipsychotic effects. Apart from the above-mentioned models of negative and cognitive symptoms, MK-801 and amphetamine-induced hyperactivity tests, plus the DOI-induced head twitches in mice as models for positive symptoms of psychosis, were used in this part of the investigations. RESULTS: LSP1-2111 (0.5, 2, and 5 mg/ kg) dose-dependently inhibited MK-801-induced deficits in social interaction and NOR tests. The effects of the drug were antagonized by 5-HT(1A) antagonist, WAY100635 (0.1 mg/kg). A similar inhibition of LSP1-2111-induced effects was observed in models of positive symptoms of schizophrenia. Moreover, the concomitant administration of subeffective doses of LSP1-2111 (0.3-0.5 mg/kg) with a subeffective dose of 5-HT(1A) agonist, (R)-(+)-8-Hydroxy-DPAT (0.01 mg/kg), induced a clear antipsychotic-like effect in all of the procedures used. CONCLUSIONS: Altogether, we propose that the activation of group III mGlu receptors may be a promising target for the development of novel antipsychotic drugs, towards not only positive but also negative and cognitive symptoms. The action of the compound is 5-HT(1A)-dependent.